The power of positive languaje; save and change lives, in the classroom - Mendoza Carrasco, Mariella Victoria (2020)
Through drawing and words, our emotions are manifested, because they express our feelings and thoughts. Using positive language brings out the best in ourselves, it has a power in our state of mind. By choosing positive words, the teacher voluntarily and with consent when addressing students on a day-to-day basis, contributes to developing their students’ self- esteem  in the classroom. In this very simple way, you can make the routine days and the environment at school; something much more enjoyable and motivating. The teacher must publicly reinforce the positive stimuli to the student and highlight with positive motivating words; highlighting your skills, abilities and skills; generating a cozy and pleasant atmosphere.